Guidebooks with recommendations for the design of teaching materials aimed for low vision public: evaluation from the Human-Centered Design perspective - Bueno, Juliana; Picelli Sanches, Emilia Christie; de Abreu Antoniolli, Karina; Reque, Marluce; Rodrigues de Lima, Caroline (InfoDesign, 2024)
A crucial step in the development of a product or system, evaluation is intrinsically linked to Design processes that start from a human-centered approach. Therefore, this article aims to present the entire development and application process of the evaluation stage from two recommendation guidebooks for the development of teaching materials aimed for the low vision public. These guidebooks were developed from an inclusive design perspective and, in this case, in addition to bringing simple content to the public, they should also meet accessibility specifications. The process had two rounds of evaluation: (1) evaluation with Design specialists and a teacher with low vision and; (2) specialist teachers in the education of people with low vision. Both brought insights for improvements on the guidebooks for the development team.